Pteris sotae (Pteridaceae), a new endemic species for the Argentinean flora - Martínez, Olga G. (Phytotaxa, 2016)
This paper describes Pteris sotae, a new endemic fern species from the Tucuman–Bolivian Forest in northwestern Argentina. This species is easily distinguished by its hairy laminae and areolate venation. A distribution map and photographs are provided.